SOCIAL REPRESENTATIONS OF HEALTH AMONG STUDENTS-ATHLETES AND STUDENTS NOT INVOLVED IN SPORTS - Zvonova, E.V.; Seryakova, S.B.; Kerimova, I.A.; Artyushkina, T.V. (Theory and Practice of Physical Culture, 2022)
Objective of the study is the content and structure of social ideas about health among students who have linked their future with professional sports, and among students who do not go in for sports. Methods and structure of the study. The research methodology was based on the main provisions of French social psychology on the phenomenon of social representations and their functions in the life of people and society (S. Moskovisi), as well as provisions on the structure of social representations (J.K. Abrik). The research methods were the SF-36 Health Status Survey Questionnaire and the methodology for studying the structure and content of social representations by P. Vergès. The study involved 56 students aged 20 to 24 years, of which 29 people are professionally involved in sports and 27 people are not involved in sports. Results and conclusions. The results of the survey showed that student-athletes have complete, evidence-based and systemic knowledge about health, about the requirements of health-saving conditions and the principles of a healthy lifestyle. However, the study of the prototype analysis data showed that for athletes, health is considered as a condition for the success of sports activities, providing a high level of physical capabilities. Such an “instrumental” approach leads to the fact that professional athletes consider health not as the most important value, but as a basic condition for sports achievements and career success. Students, participants of the study who are not involved in professional sports, have poorly structured knowledge about the essence of a healthy lifestyle, tend to give stereotypical answers. However, their social representations consider health as a necessary condition for a happy life, associated with activity and general well-being.